Strategi Baitul Mal Wattamwil (BMT) Al-Hikmah Bandar Lampung dalam Meningkatkan Kemandirian dan Ketahanan Ekonomi Keluarga - Masmuroh Masmuroh; Sukri Sukri; Ramli Ramli; Iin Meriza (Empower : Jurnal Pengembangan Masyarakat Islam, 2023)
Social development can be carried out in various fields of community life, one of which is economic growth that develops based on the independence of each person. The Islamic Boarding School through the Savings and Loans Cooperative and Sharia Financing (KSPPS) BMT Al-Hikmah is aware of these challenges and then moves to empower all opportunities that exist in society. This study aims to determine the strategy of Baitul Mal Wattamwil (BMT) Al-Hikmah Bandar Lampung in increasing family economic independence and resilience. The method used in this research is descriptive qualitative with data collection techniques of interviews, observation, and documentation. The results of the Baitul Mal Wattamwil (BMT) Al-Hikmah Bandar Lampung strategy research in increasing family economic independence and resilience through the potential of independent entrepreneurs in increasing family resilience. The strategy includes 4 empowerment programs such as 1) Development of Human Resources (HR); 2) Group Institutional Development; 3) Fostering Community Capital; and 4) Productive Business Development. The impact of the implemented strategy is the solution to various problems faced by the community to increase income and financial well-being as well as family resilience.